Drug-Resistant Tuberculosis and COVID-19: A Scoping Review on a New Threat to Antimicrobial Resistance - Beibilene Perlato Melo da Silva; Anelisa Soares de Almeida; Matheus Gabriel de Melo Sérgio; Thamires Carraro Gatto; Vinícius Paglione Carasek; Mellina Yamamura (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To assess the impact of COVID-19 on the morbidity and mortality associated with drug-resistant tuberculosis (DR-TB). Methods: A comprehensive review of articles published in international databases since December 2019 was conducted. The findings are presented in a narrative format, supplemented with tables, diagrams, and a map created using ArcGIS software. Results: Thirty-five studies were selected, highlighting the significant consequences of COVID-19 on TB and DR-TB treatment progress. Four main thematic areas were identified: Clinical and epidemiological aspects of the interaction between COVID-19 and DR-TB; Management of physical resources and the team; Challenges and circumstances; Perspectives and possibilities. Conclusions: This study revealed that the COVID-19 pandemic significantly negatively impacted the control of long-standing diseases like TB, particularly in the context of morbidity and mortality related to DR-TB.